Manajemen Pendidikan Perempuan Pada Masa Sultan Syarif Kasim II di Kesultanan Siak Sri Indrapura Tahun 1927-1945 - Annisaa Ambarnis; Wawan Darmawan; Yani Kusmarni (Diakronika, 2023)
This research is motivated by the researcher's interest in the development of women's education in the Siak Sultanate, to be precise, during the reign of Sultan Syarif Kasim II. The main problem studied in this research is how to manage women's education to the realization of educational outcomes in women's schools formed by Sultan Syarif Kasim II in 1927-1945. In general, this study aims to describe the pattern of women's education formed by Sultan Syarif Kasim II and his consort in the Siak Sultanate. This study was studied by applying historical methods, including four steps, namely heuristics, verification, interpretation, and historiography. Based on the research findings, the pattern of women's education in Siak Sri Indrapura was formed directly by the sultanate including the formation of the curriculum, procurement of teachers and students and the facilities provided. Although both were managed by the sultanate, there were different styles of teaching between the two women's schools founded by Sultan Syarif Kasim II, namely Sultanah Latifah School which focused more on teaching hand skills and homemaking, and Madrasa Annisa which taught more Islamic religious knowledge. The results of the education of the two girls' schools gave birth to women who were prosperous in terms of changes in social institutions, which succeeded in becoming a weaver, educator, and preacher. Thus the management of education formed by Sultan Syarif Kasim II succeeded in contributing greatly to the welfare of women's education in the Sultanate of Siak Sri Indrapura